Manejo de plagas de la quinua para una agricultura orgánica - Delgado Mamani, Pedro; Goyzueta Hancco, Washington; Farfán Loaiza, Danilo; Chura Parisaca, Eusebio (Instituto Nacional de Innovación Agraria, 2021)
40 páginas